Determining the degree of acetylation of chitin/chitosan using a SSNMR 13C method on the basis of cross polarization reciprocity relation. (December 2020) - Tang, Dandan; Qian, Jianying; Wang, Ning; Shu, Jie
Abstract: The degree of acetylation (DA) is an essential parameter for chitin and its derivatives, which determines the chemical and physical properties of the polymers. As a consequene, fast and accurate technique to determine DA is widely required when developing the relating materials. Herein, an improved quantitative SSNMR method of rQCPZ RC, based on the cross polarization reciprocity relation, was discussed and employed for DA testing. Three chitin/chitosan samples were chosen to evaluate the performance of rQCPZ RC . In comparison with quantitative DP and optimized contact time CP methods, rQCPZ RC is revealed as an accurate and reliable DA testing method with relative percentage errors of less than 5%. Moreover, the experimental time of rQCPZ RC for each sample is 5.5 h, notably shorter than DP of 36–85 h. Thus, our work suggests rQCPZ RC as a tool for DA testing, which is capable to accomplish with high accuracy and efficiency. Graphical abstract: Image 1 Highlights: Verify the feasibility of cross polarization reciprocity relation for the overlapped signals. Reveal the high accuracy and reliability of rQCPZ RC method for determining the degree of acetylation of Chitin and Chitosan. Reveal the notably higher efficiency of rQCPZ RC method in comparison with the traditional method of DP for DA measurement.